FACTORS RELATED TO BEHAVIOR OF UTILIZING NATIONAL HEALTH INSURANCE IN KUMUN PUBLIC HEALTH CENTER IN 2021 - Hubaybah Hubaybah; Andika Rahmat; Adila Solida; Fitria Eka Putri; Adelina Fitri (Lembaga Pengembangan Kinerja Dosen, 2022)
Background:Puskesmas in the JKN/BPJS system have a major role in health services. If the puskesmas services provided are good, then JKN participants will use health services more at the puskesmas. Puskesmas Kumun is one of the puskesmas that has a wide working area and serves 9 villages. The number of BPJS participants in puskesmas has reached 61%, but the use of national health insurance shows a less percentage. The purpose of this study was to determine the factors associated with the use of national health insurance at the Kumun Health Center. Method: This type of research is a quantitative study using a cross sectional approach, with a sample of 100 samples. This research was conducted in the district of Kumun Debai. Sampling with accidental sampling technique. Data obtained by filling out questionnaires by respondents. Data analysis was performed using univariate and bivariate (chi-square) tests. Result:Based on the statistical test in this study, it showed that the factors related to the utilization of the national health insurance were knowledge (p=0.019), education (p=0.000), occupation (p=0.013), income (0.011), and health facilities. And there is no relationship between attitude (p = 0.069), and trust (p = 0.054) with the use of the national health insurance. Conclusion: There is a relationship between the variables of knowledge, education, occupation, income, and health facilities with the use of national health insurance at the Kumun Community Health Center in Sungai Penuh City.